Shear stress increases cytotoxicity and reduces transfection efficiency of liposomal gene delivery to CHO-S cells - Rawat, Jyoti; Gadgil, Mugdha (Cytotechnology, 2016)
Animal cells in suspension experience shear stress in different situations such as in vivo due to hemodynamics, or in vitro due to agitation in large-scale bioreactors. Shear stress is known to affect cell physiology, including binding and uptake of extracellular cargo. In adherent cells the effects of exposure to shear stress on particle binding kinetics and uptake have been studied. There are however no reports on the effect of shear stress on extracellular cargo delivery to suspension cells. In this study, we have evaluated the effect of shear stress on transfection of CHO-S cells using Lipofectamine 2000 in a simple flow apparatus. Our results show decreased cell growth and transfection efficiency upon lipoplex assisted transfection of CHO-S while being subjected to shear stress. This effect is not seen to the same extent when cells are exposed to shear stress in absence of the lipoplex complex and subsequently transfected, or if the lipoplex is subjected to shear stress and subsequently used to transfect the cells. It is also not seen to the same extent when cells are exposed to shear stress in presence of liposome alone, suggesting that the observed effect is dependent on interaction of the lipoplex with cells in the presence of shear stress. These results suggest that studies involving liposomal DNA delivery in presence of shear stress such as large scale transient protein expression should account for the effect of shear during lipoplex assisted DNA delivery.